(untitled) (Research, Society and Development, 2022)
Objective: Describe the nurses’ knowledge about integrative and complementary practices in the network. Materials and methods: Methodology: This is a descriptive and transversal study, carried out in Olinda-PE. Nurses who work in Family Health Units in that municipality were included. Data collection took place between April and May 2020 using a semi-structured form. The data were tabulated in Microsoft Excel 2013 and analyzed descriptively. Results: 40 nurses participated in the study, 92.5% of whom were female. 72.5% of these professionals did not have disciplines of integrative practices at graduation. Therapeutic practices reported as the best known were acupuncture (87.5%) and yoga (87.5%), although they were only prescribed by only 10% of professionals. Conclusion: The nurses’ knowledge made it possible for only 32.5% to make referrals and only 50% claim to have a referral network in the municipality where they work. In-service training could facilitate users’ access, since most professionals point out that they would like to enable them in the municipality where they work.